Польсько-українська дискусія щодо подій на Волині у роки Другої світової війни: здобутки та труднощі - Стрільчук, Людмила Василівна; Strilchuk, Liudmyla V. (My University, 2018)
Однією з найпроблемніших сторінок польсько-української спільної історії є міжнаціональні взаємини українців і поляків періоду Другої світової війни, що відомі широкому загалу, як "Волинська трагедія". В останні роки між Україною та Республікою Польща виникає чимало суперечок з приводу оцінки причин та перебігу міжнаціонального конфлікту на Волині 1943-1944 років, підрахунку кількості жертв політичних спекуляцій і негативно впливає на сучасні міжнародні взаємини. Пошук шляхів щодо трансформації історичної пам’яті українців та поляків, згладження міжнаціональних протиріч, полягає у різнобічному незаангажованому висвітлені усіх аспектів проблеми та подоланні негативних суспільно-історичних стереотипів, що мають місце в обох суспільствах.

The interethnic relations between Ukrainians and Poles in the period of the Second World War, known to the general public as "Volyn tragedy", is one of the most problematic pages of the joint Polish-Ukrainian history. In recent years there has been a lot of controversy between Ukraine and the Republic of Poland over the assessment of the causes and development of the inter-ethnic conflict in Volyn in 1943-1944, calculation of the number of victims of the conflict and the issues of interpretating the events of common history. The problem in question has become the subject of political speculations and negatively affects modern interethnic relations. The search for the ways to transform the historical memory of Ukrainians and Poles and to eliminate interethnic contradictions implies the multifaceted, unbiased elucidation of all aspects of the problem and surmounting the negative socio-historical stereotypes that occur in both societies.
Polish-ukraine discussion on events in the folk in the years of the second world war: gifts and difficulties
Keywords: історична пам'ять; міжнаціональний конфлікт; Волинь; Друга світова війна; дискусія; historical memory; interethnic conflict; Ukrainians; Poles; Volyn; Second World War; discussion